Characterization & antibacterial activity of goat’s milk soap enriched with piper betle leaf powder - Ali, Rosliza; Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Yaacob, Yanti (2024)
The aims of this study are to optimize the best formulation of goat’s milk soap enriched with Piper betle leaf powder and to investigate the antibacterial activity against Staphylococcus epidermidis. In this study, four goat’s milk soap samples were prepared with different ratios. These soaps were characterized for its organoleptic properties, pH, allergy test and antibacterial activity. The antibacterial activity was assessed by measuring the inhibition zones around the bacterial cultures using the agar-well diffusion method. The findings reveal that the inclusion of Piper betle leaf powder did not demonstrate antibacterial activity against Staphylococcus epidermidis.